นักการเมืองและโครงสร้างอำนาจในจังหวัดสมุทรปราการ - กฤตยาณี พิรุณเนตร (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This study is a qualitative study, with the objective to 1) to study the economic and social changes in the Samut Prakan province. 2538 (1995) range-2555 (2012) 2) to study the role of the traditional group of politicians in the province of Samut Prakan that is changed. How to study 3) the relationship of the economic and social changes in the province of Samut Prakan with the emergence of a new group of politicians. In this way, the study of descriptive analysis based on the collection of documents to research the concept of theory and related research and in-depth interviews. From the study of economic and social conditions found in Samut Prakan province. Has been developed continuously by the apparent. From the continuous rise of the gross product of the province. Whether it is the agricultural sector or industry sector. With the expansion of housing, including an increase of population in the province of Samut Prakan on payment calculator. In the traditional group of politicians. After Mr. Wattana Assawaheam The head of the Assawaheam Group lost general election and corruption cases to the subject land, 2544 (2001) Klong Dan. Make Mr. Wattana Assawaheam and Assawaheam Group, There are no political roles in Samut Prakan. Although a political role in national politics of the Assawaheam Group is very lower, however, still have a role in the politics of local is very different. The section on the story of the emergence of a new political group. Play a role in politics after being general election in history since 2544 (2001) because, economic and social changes. As a result, the concept of change. People focus on the policies of political parties, which are considered the benefits that people receive from political parties has caused Thai Rak Thai party be popular. Thus leading to the emergence of a new political group in the Samut Prakan province.